Process for producing environment-friendly baking-free brick - YUE ZUOXING (2017)
The invention discloses a process for producing an environment-friendly baking-free brick. The process comprises the following steps: weighing and mixing cement, calcium carbonate, ash, slaked lime, excitant and a curing agent in a mixing proportion to form a mixture; stirring and mixing the mixture in a stirrer, and stirring with water to uniformly stir the material with water to prepare a mixed material; putting the mixed material in a mold, and press-molding the mold in a hydraulic machine to prepare an environment-friendly baking-free brick; and maintaining the brick. The baking-free brick produced by adopting the production process has the advantages of high compressive strength, high breaking strength and good freeze thawing performance, and has huge market potential and wide prospect. 本发明公开了种环保型免烧砖的生产工艺，将水泥、碳酸钙、灰渣、熟石灰、激发剂和固化剂，按混合比例进行称量配制，形成混合料；将配制好的混合料，置于搅拌器内进行搅拌混合，然后加入水进行搅拌，使物料与水分搅拌均匀，制得混合物料，将混合物料布于模具中，接着将模具置于液压机下压制成型，制得环保型免烧砖坯，同时对其进行养护，采用此种生产工艺生产出来的免烧砖具有抗压和抗折强度高以及冻融性好的优点，市场潜力巨大，前景广阔。